The right to information as the basis of media activity in Ukraine - Pivneva, Lyubov (ScienceRise: Juridical Science, 2021)
The article identifies some approaches to identifying the concepts of media and legal information. Some classifications of mass media and their immanent elements are considered. The concept of information and its qualifying legal features are defined. The main Laws of Ukraine concerning information are highlighted. Separate normative-legal laws of Ukraine on information and various forms of information are singled out. Categories of legal, public information and misinformation are considered. The key Law of Ukraine on information dated October 2, 1992 № 2657-XII has been determined. It is investigated, that the main source of legal information is the Constitution of Ukraine in accordance to the Law of Ukraine "On Information". It is proved, that information can exist in an ideal and material form and be the object of commodity relations. Attention is drawn to the Law of Ukraine "On Electronic Documents and Electronic Document Management". It is proved, that in the era of using information and communication technologies, the implementation of e-government makes it possible to operate in an information society. Sources for media information have been identified - state, confidential and anonymous. Attention is drawn to the access of the media to confidential information, to data that are not disclosed or published only by court decision. An example is given of the possibility of disseminating public or private information about a person. Attention is drawn to the need to verify anonymous information. In conclusion, it is emphasized, that the media in Ukraine are trying to follow in the footsteps of the latest information and communication technologies. The use of constitutional and legal acts is a vital necessary condition for building civil society, guaranteeing the constitutionality of democracy, freedom of access of the media to primary sources of information.